Hypoglycemia unawareness among insulin-treated diabetic patients in Madinah, Saudi Arabia: prevalence and risk factors - Surrati, Amal M. Qasem; Alanazi, Alhanouf Ayed; Bukhari, Samyah Sami; Alfadhli, Eman Mohammed (Frontiers in Endocrinology, 2023)
Background Hypoglycemia unawareness (HU) is associated with significant risks. Screening for impaired awareness of hypoglycemia in patients with diabetes is important to minimize those risks. There are limited data on the prevalence of HU in patients with diabetes in Saudi Arabia (KSA). In the current study, we investigated the frequency of HU and its risk factors among insulin treated diabetic patients in Madinah, KSA. Methods A cross-sectional study was conducted in a diabetes center and four primary healthcare centers at Madinha, KSA. Patients ≥14 years old with type 1 or type 2 diabetes treated with insulin for more than a year were included. HU was assessed by Clarke’s and modified Pedersen-Bjergaard’s scores. The risk factors for HU were determined. Results Of the 413 included patients, 60.3% were women, and 60.8% were on insulin alone. One-third of the participants had T1DM, while 68.5% had T2DM, with median ages of 25 and 56 years, diabetes durations of 10 and 15 years, and durations of insulin use of 10 and 5 years, respectively. The prevalence of HU was 25.2% by Clarke’s survey. The risk factors for HU were poor knowledge of the patient’s latest HbA1c, type of insulin, and dose of insulin. Poor medical follow-up, previous stroke, and ischemic heart disease were the other risk factors for HU. When the modified Pedersen-Bjergaard method was used, the prevalence of HU was 48.9%. Conclusion Despite the advances in diabetes management, HU continues to be prevalent among diabetic patients on insulin, and poor diabetes knowledge is a major risk factor. Diabetes education on self-management is of utmost importance to reduce hypoglycemia and HU.